Social Movements and Politics in a Global Pandemic Crisis, Solidarity and Change during COVID-19 - Bringel, Breno; Pleyers, Geoffrey (Bristol University Press, 2022)
EPUB and EPDF available Open Access under CC-BY-NC-ND licence. The COVID-19 pandemic has deeply shaken societies and lives around the world. This powerful book reveals how the pandemic has intensified socio-economic problems and inequalities across the world whilst offering visions for a better future informed by social movements and public sociology. Bringing together experts from 27 countries, the authors explore the global echoes of the pandemic and the different responses adopted by governments, policy makers and activists. The new expressions of social action, and forms of solidarity and protest, are discussed in detail, from the Black Lives Matter protests to the French Strike Movement and the Lebanese Uprising. This is a unique global analysis on the current crisis and the contemporary world and its outcomes.EPUB and EPDF available Open Access under CC-BY-NC-ND licence. The COVID-19 pandemic has deeply shaken societies and lives around the world. This powerful book reveals how the pandemic has intensified socio-economic problems and inequalities across the world whilst offering visions for a better future informed by social movements and public sociology. Bringing together experts from 27 countries, the authors explore the global echoes of the pandemic and the different responses adopted by governments, policy makers and activists. The new expressions of social action, and forms of solidarity and protest, are discussed in detail, from the Black Lives Matter protests to the French Strike Movement and the Lebanese Uprising. This is a unique global analysis on the current crisis and the contemporary world and its outcomes.